The colonial legacy of Mooi Indië and the captive mind in the environmental policy of Citarum Harum - Hapsoro, Chabib Duta; Yeru, Aulia Ibrahim (Wacana, Journal of the Humanities of Indonesia, 2022)
Mooi Indië paintings represented the orientalist-colonial imagination of the picturesque Netherlands East Indies, with the obfuscation of the social realities on the ground and the silencing of the adverse effects of colonial capitalism. This article discusses the colonial legacy of Mooi Indië paintings on contemporary environmental policy in Indonesia, with a case study of the policy of the Citarum Harum Taskforce. This Taskforce was formed in 2018 and marked the national government’s attempt to rehabilitate the Citarum after it was declared one of the most polluted rivers in the world. It provides an analysis of several Mooi Indië paintings which depict the Citarum River and were created by European painters (such as Antoine Payen and Isaäc Groneman), before looking at the contemporary effects of the Citarum Harum’s beautification-oriented policy. The article also analyses some particular stereotypes of Netherlands East Indies natives as depicted in Mooi Indië paintings for comparison with the Taskforce’s policy implementation on the residents along the Citarum River. Ultimately, such a comparison demonstrates a form of colonial captivity at work today. The ideas of the Citarum Harum Taskforce demonstrate a captive mind, which continues to hide the socio-environmental problems which persist. This to the exploitation of the environment and people in the wake of the contemporary neoliberal system which dominates our worldview.